Incidencia del ecoperiodismo en la calidad de vida de las mujeres que laboran en la tabacalera Karlita Recinto Relampago, cantón Urdaneta, 2022 - Pincay Macias, Iris Michelle (2022)
The purpose of this study was to demonstrate the existence of improvement in the quality of life of women who are working within the Relámpago tobacco company. To achieve this objective, we worked through Ecojournalism, which deals with the interrelationships and changes that arise between the human being and the environment that surrounds him. Descriptive research was applied, where the observation and description of the behavior of women in their environment was a fundamental pillar in obtaining the necessary information to achieve the purpose of the research. The most relevant conclusion of the research was that there is an improvement in the quality of life, despite family pressure, the machismo present in the society of the sector, limit the participation of women and slow down the desired change.